Supramolecular aggregation patterns in the crystal structures of the dinuclear phosphinegold(i) thiolates, (Ph2P(CH2) 4PPh2){AuSC(OR)=NC6H4Y-4} 2 for R = Me, et or iPr and y = H, NO2 or Me: The influence on intermolecular interactions exerted by R and y - Ho, S.Y. (2014)
10.1039/b700295e